COGNITIVE CONSIDERATION IN PERSUADING READERS IN ARGUMENTATIVE WRITING - Betharia Br. Sembiring Pandia; Berlin . Sibarani; Sumarsih . . (LINGUISTIK TERAPAN, 2021)
The objectives of this study was to describe the writers’ ways of persuading readers in argumentative writing. This study followed the theory of Ramage et.al. (2016) about the ways of persuading readers which comprises of text structure, reasoning, and persuasive appeal. This study used descriptive qualitative design. The data of this study were gathered by using elicitation technique, asking the 8th semester of undergraduate students to write argumentative text under predetermined topic Social Media Should be Banned with three intended readers, they were: Junior High School, Senior High School, and Undergraduate students.This study revealed that the subjects manipulated the text structure by presenting three-layered text structure of argumentative writing, and presenting the pseudo-evidence and organizing cause and effect relationship in terms of the reasoning aspect.Keywords: Cognitive Consideration, Argumentative, Writing, Persuasive